Structured COBOL Programming / Sixth Edition - Stern Nancy; Stern Robert (John Wiley & Sons, Ltd, 1991)
Notes, The Basics, Designing Structured Programs, Writing High-Level COBOL Programs, Array Processing and Table Handling, File Maintenance, Advanced Topics, Appendixes, Index.